Soil basics, management and rhizosphere engineering for sustainable agriculture - Channarayappa; Biradar, D. P. (Boca Raton, FL : CRC Press, 2019)
Increase in global population, drastic changes in the environment, soil degradation and decrease in quality and quantity of agricultural productivity warranted us to adapt sustainable farming practices. This book focuses on soil health management and creating biased rhizosphere that can effectively augment the needs of sustainable agriculture.
OCLC-licensed vendor bibliographic record.
Keywords: Soil management; Soil management -- Environmental aspects; Sustainable agriculture; Rhizosphere; TECHNOLOGY & ENGINEERING -- Agriculture -- General